Influence of intergenerational in utero parental energy and nutrient restriction on offspring growth in rural Gambia. Issue 11 (4th August 2017) - Eriksen, Kamilla G.; Radford, Elizabeth J.; Silver, Matt J.; Fulford, Anthony J. C.; Wegmüller, Rita; Prentice, Andrew M.
Abstract : The prenatal environment can alter an individual's developmental trajectory with long‐lasting effects on health. Animal models demonstrate that the impact of the early life environment extends to subsequent generations, but there is a paucity of data from human populations on intergenerational transmission of environmentally induced phenotypes. Here we investigated the association of parental exposure to energy and nutrient restriction in utero on their children's growth in rural Gambia. In a Gambian cohort with infants born between 1972 and 2011, we used multiple regression to test whether parental season of birth predicted offspring birth weight ( n = 2097) or length ( n = 1172), height‐for‐age z score (HAZ), weight‐for‐height z score (WHZ), and weight‐for‐age z score (WAZ) at 2 yr of age ( n = 923). We found that maternal exposure to seasonal energy restriction in utero was associated with reduced offspring birth length (crude:−4.2 mm, P = 0.005; adjusted: −4.0 mm, P = 0.02). In contrast, paternal birth season predicted offspring HAZ at 24 mo (crude: −0.21, P = 0.005; adjusted: −0.22, P = 0.004) but had no discernible impact at birth. Our results indicate that periods of nutritional restriction in a parent's fetal life can have intergenerational consequences in human populations. Fetal growth appears to be under matriline influence, and postnatal growth appears to be under patriline intergenerational influences.—Eriksen, K. G., Radford, E. J., Silver, M. J., Fulford, A. J. C., Wegmüller, R., Prentice, A. M. Influence of intergenerational in utero parental energy and nutrient restriction on offspring growth in rural Gambia. FASEB J. 31, 4928–4934 (2017). www.fasebj.org